A Novel Integrating Between Tool Path Optimization Using An ACO Algorithm And Interpreter For Open Architecture CNC System - Yusof, Yusri; Latif, Kamran; Hatem, Noor; A. Kadir, Aini Zuhra; Mohammed, M.A (Elsevier, 2021)
This article proposes an effective methodology to reduce manufacturing time through the creation of quasioptimal G command sequences, based on initial machining codes derived from CAD/CAM Service-Oriented Architecture (SOA) software. The optimization steps involved minimizing travel path time for CNC manufacturing machine milling and drilling. Also, identifying the optimal order of operation that enabled the shortest travel path for the cutting tool. These steps resulted in consistent enhancements of approximately 10.41% and 16.58% for milling and drilling machining, respectively. Furthermore, high-performing Ant Colony Optimization (ACO) algorithms were used to optimize the travel path time. In the context of automatic NC program production, the optimization of the cutting tool’s travel path could be achieved by integrating the ACO algorithm and the Open Architecture Control (OAC) into commercial CAD/CAM. In this paper, a new optimized generation of CNC systems, based on combining the Open Architecture Control (OAC) technology supported by the G-code data model and the optimization algorithm are presented